(untitled) (NTU Journal of Agriculture and Veterinary Science, 2024)
Mycoplasma cynos is a member of the class Mollicutes. It is more pathogenic, more host specific than other canine Mycoplasma, and only associated with respiratory diseases in dogs due to producing many virulence factors, recently neuraminidase and hemagglutinin. The study was done to detect the neuraminidase and hemagglutinin of Mycoplasma cynos isolated from the upper respiratory tract and conjunctival infections in household dogs. Mycoplasma isolates obtained from nasal, oropharyngeal, and conjunctival swabs from household dogs suffering from respiratory diseases in different veterinary clinics in Mosul city. DNA extraction was prepared , PCR and sequencing of 16S rRNA, then Mycoplasma cynos was examined for neuraminidase and hemagglutinin using specific primers.The results showed the identification of Mycoplasma cynos strain "SM-MY-M23" under accession number“OQ446513” in percentage (67.6%), and detection of neuraminidase only. Results obtained are considered the first record of M. cynos and the important virulence factor (Neuraminidase) from household dogs in Iraq.